Memory Mass Storage - Campardo, Giovanni; Tiziani, Federico; Iaculo, Massimo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Memory Mass Storage describes the fundamental storage technologies, like Semiconductor, Magnetic, Optical and Uncommon, detailing the main technical characteristics of the storage devices. It deals not only with semiconductor and hard disk memory, but also with different ways to manufacture and assembly them, and with their application to meet market requirements. It also provides an introduction to the epistemological issues arising in defining the process of remembering, as well as an overview on human memory,  and an interesting excursus about biological memories and their organization, to better understand how the best memory we have, our brain, is able to imagine and design memory.
What is a memory, that it may comprehend itself? Self-referential implications of the phenomenology of remembering -- Mass storage memory market biography -- Probe Storage -- Modern Hard Disk Drive Systems: Fundamentals and Future Trends -- Introduction to SSD -- Package Trends and Technology into Wireless and SSD Applications -- High Capacity NAND Flash memories: XLC storage and single-die 3D -- Optical Data Storage -- Biological Memory in Animals and in Man -- Memories for everybody.
Keywords: Electronic circuits; Circuits and Systems